Estimation of Genetic Parameters for Egg Production and Clutch Traits in Lindian Chickens - Jiacheng Liu; Fei Liang; Changsheng Sun; Xu Wang; Zhiyong Su; Yumao Li; Peng Luan; Zhiping Cao; Xue Bai; Li Leng (Animals, 2025)
To accelerate breeding progress for egg production traits in Lindian chickens, the genetic parameters for egg production and clutch-related traits in Lindian chickens were evaluated in the present study. Data regarding the age at first egg (AFE), egg number (EN), average clutch length (ACL), and average pause length (APL) were collected from two generations of Lindian chickens based on individual egg production records at 32 weeks of age (32–wk), 43–wk, and 52–wk. The results showed that the AFE of Lindian chickens was 179.3 d of age, with a heritability of 0.35. The heritability was 0.26 for EN32, 0.28 for EN43, and 0.34 for EN52. ACL showed moderate-to-high heritability (h2 = 0.3–0.54), but APL traits showed low heritability (h2 = 0.09–0.14). There were high positive genetic and phenotypic correlations for EN in the three periods from the start of laying up to 32–wk, 43–wk, and 52–wk. EN had high negative genetic correlations with AFE (rG = −0.47–−0.80) and high positive genetic correlations with ACL (rG = 0.45–0.81). The correlation between EN and APL was positive for 32–wk and 43–wk, but negative for 52–wk. These results indicated that the egg production of Lindian chickens could be improved by the selection of AFE, early EN, and ACL.